Definição automática de áreas censitárias na freguesia de Algés - Mileu, Nelson (Finisterra, 2003)
AUTOMATIC STATISTICAL AREA DEFINITION IN ALGÉS PARISH. Portugal, along with many other countries, conducts a population census every 10 years. This way of counting the population offers a detailed photography of the country where many socio-economic variables are captured. In this study, it is assumed that census will be the way of population data collection and therefore the discussion deals with the issue of geographical aggregation of individuals and households enumerated. In this context, a methodological proposal for an automatic census area creation in the parish of Algés is described. The minimum geographic unit for completing the aggregations is the building since it was the smallest and stable unit for this purpose. The building layer was obtained in the municipal GIS of Oeiras and is based on large scale cartography (1:1000). Mainly, because the building layer is not contiguous, the study starts with the construction of a Thiessen polygon layer. This layer is drawn with the buildings layer centroids and having the master plan classes as barriers. The Thiessen polygon layer associated with the building attributes assumed a key role in this process and considering the range of possible data aggregation alternatives the zone boundaries are drawn concerning with some principles of consistence and homogeneity. To achieve a measurement of homogeneity for the statistical areas the variables used were the number of households, floors and type of building (residential, commercial, both). The automatic statistical area definition deals with the aggregation of the basic geographic units (Thiessen polygon layer), seeking for new optimized areas, considering the characteristics of the building and having a reference number of households around 100. To demonstrate the methodology used for the automatic statistical area definition, three simulation results are presented in this article.